Energy- and Spectral-Efficiency Trade-Off in OFDMA-Based Cooperative Cognitive Radio Networks - Xiaomao Chen; Shan Ouyang (International Journal of Distributed Sensor Networks)
We study the trade-off between energy efficiency (EE) and spectral efficiency (SE) in cooperative cognitive radio networks (CCRN); joint power and subcarrier allocation scheme is proposed. Resource is assigned to each user in a way which ensures maximizing energy efficiency, maintaining primary and second user quality of service (QoS) requirements. Optimum transmit power of user is got by analysis; validity of theory is verified by simulation, and the proposed algorithm can adaptively allocate resource for CCRN.